Norway : Financial Sector Assessment Program-Technical Note-Systemic Risk Oversight and Macroprudential Policy Framework. (IMF Staff Country Reports; Country Report ;, 2020)
While Norway's institutional arrangement for macroprudential policy is uncommon, the authorities have shown strong willingness to act. The Ministry of Finance (MoF) is the sole macroprudential decision-maker in Norway, which is rare in international comparison. However, Norges Bank and the Finanstilsynet (FSA) play important advisory roles. In recent years, the authorities have taken substantive and wide-ranging macroprudential policy actions in response to growing systemic vulnerabilities-and these seem to have been effective in slowing down some of the riskier trends. The macroprudential policy toolkit is well stocked and actively used.